Rihlat fi eaql namla - Al-Mashali, Hoda; Zahdi, Amer (Sharjah, United Arab Emirates : Nabdh Al Qalam Books Publishing and Distribution, 2020)
Educational and awareness stories
Keywords: Arabic language -- Readers -- Fiction; Children's stories, Arabic